Time-Series Transcriptomics of a Gill Cell Line (BTG) from Chinese Bahaba (Bahaba taipingensis) During ISKNV Infection (3–24 hpi) - Chenfei Guo; Zhihong Gong; Fei Fang; Xihong Li; Lei Wang; Na Wang; Zhangfan Chen; Lin Yan; Kuoqiu Yan; Guobin Hu; Songlin Chen (Fishes, 2026)
The Chinese bahaba (Bahaba taipingensis), an endangered marine fish, is highly vulnerable to infectious spleen and kidney necrosis virus (ISKNV). In this work, we developed a gill filament-derived cell line, designated BTG, to investigate how these cells respond to ISKNV over time, specifically from 3 to 24 h post-infection (hpi). BTG cells grew steadily, displayed a diploid chromosome number of 2n = 48, demonstrated high transfection efficiency, and were highly susceptible to viral infection. Characteristic cytopathic effects (CPEs) became noticeable as early as 6 hpi at 27 °C. RNA-seq profiling showed that the number of differentially expressed genes (DEGs) steadily increased with time. Standard enrichment analysis at individual time points (3, 6, 12, and 24 hpi) highlighted pathways mainly involved in DNA replication, cell cycle control, ribosome assembly, transcription and translation, mismatch repair, and cell adhesion. Temporal clustering analysis, however, revealed hidden patterns in immune gene expression. Genes that were consistently downregulated were enriched in immune-related pathways, including ECM–receptor interaction, cytokine–receptor signaling, PI3K–AKT, and Wnt signaling, indicating prolonged suppression of host defense mechanisms. In contrast, clusters of genes transiently upregulated during the first 6 h post-infection were associated with antiviral and innate immune pathways, such as NF-κB, JNK, IRF3, IRF7, caspases, JAK, MHC I, and lysosome-related functions, suggesting a rapid but short-lived antiviral response. Genes that were continuously upregulated were primarily involved in nucleic acid replication and protein synthesis, reflecting a gradual host cell reprogramming to support viral replication. Taken together, these findings reveal a temporal shift in BTG cells from an initial burst of immune activity to immune suppression, accompanied by enhanced viral replication. The BTG cell line thus represents a valuable in vitro model for dissecting ISKNV–host interactions and offers new perspectives on the molecular strategies employed by megalocytiviruses in B. taipingensis.